Accuracies and costs of prediction and mapping soil properties using proximal sensors: A systematic review - Carlos Lozano-Fondón; Romina Lorenzetti; Roberto Barbetti; Konrad Metzger; Gabriele Buttafuoco; Melis Özge Pinar; Sevinç Madenoğlu; Taru Sandén; Asa Gholizadeh; Bo Stenberg; Maria Fantappiè; Fenny van Egmond; et al. (Computers and Electronics in Agriculture, 2026)

Perennial flower strips increase pollinator and natural enemy abundance but have limited effects on pest control in adjacent crops - Neus Rodríguez-Gasol; Maria Viketoft; Elodie Chapurlat; Johan A. Stenberg; Mattias Jonsson; Ola Lundin (Agriculture, Ecosystems & Environment, 2026)

Political deafness may impede transition to biological control - Johan A. Stenberg; Paul G. Becher; Mattias Jonsson; Magnus Karlsson; Ingvar Sundh; Maria Viketoft (Trends in Plant Science, 2023)

Correction to: When is it biological control? A framework of definitions, mechanisms, and classifications - Johan A. Stenberg; Ingvar Sundh; Paul G. Becher; Christer Björkman; Mukesh Dubey; Paul A. Egan; Hanna Friberg; José F. Gil; Dan F. Jensen; Mattias Jonsson; Magnus Karlsson; Sammar Khalil; et al. (Journal of Pest Science, 2021)

When is it biological control? A framework of definitions, mechanisms, and classifications - Johan A. Stenberg; Ingvar Sundh; Paul G. Becher; Christer Björkman; Mukesh Dubey; Paul A. Egan; Hanna Friberg; José F. Gil; Dan F. Jensen; Mattias Jonsson; Magnus Karlsson; Sammar Khalil; et al. (Journal of Pest Science, 2021)
Biological control , or biocontrol , is the exploitation of living agents (incl. viruses) to combat pestilential organisms (incl. pathogens, pests, and weeds) for diverse purposes to provide human benefits. Thus, during the last century the practices and concepts involved have evolved in separate streams associated with distinct scientific and taxonomic disciplines. In parallel developments, there have been increasing references to biological control in industrial contexts and legislation, resulting in conceptual and terminological disintegration. The aim of this paper is to provide a global conceptual and terminological platform that facilitates future development of the field. We review use of previously suggested terms in key fields (e.g., phytopathology, entomology, and weed science), eliminate redundant terminology, identify three principles that should underpin the concept, and then present a new framework for biological control, rooted in seminal publications. The three principles establish that (1) only living agents can mediate biological control, (2) biological control always targets a pest, directly or indirectly, and (3) all biocontrol methods can be classified in four main categories depending on whether resident agents are utilized, with or without targeted human intervention ( conservation biological control and natural biological control , respectively) or agents are added for permanent or temporary establishment ( classical biological control and augmentative biological control , respectively). Correct identification of what is, and is not, biological control can help efforts to understand and optimize biological pest control for human and environmental benefits. The new conceptual framework may contribute to more uniform and appropriate regulatory approaches to biological control, and more efficient authorization and application of biocontrol products.

Paths to a sustainable food sector: integrated design and LCA of future food supply chains: the case of pork production in Sweden - Ulf Gunnar Sonesson; Katarina Lorentzon; Annica Andersson; Ulla-Karin Barr; Jan Bertilsson; Elisabeth Borch; Carl Brunius; Margareta Emanuelsson; Leif Göransson; Stefan Gunnarsson; Lars Hamberg; Anna Hessle; et al. (The International Journal of Life Cycle Assessment, 2016)

Nitrogen management strategies in organic winter oilseed rape (Brassica napus L.) production - Maria Stenberg; Lena Engström; Ann-Charlotte Wallenhammar; Ingemar Gruvaeus; Pär-Johan Lööf (Organic Agriculture, 2013)

Mulch N recycling in green manure leys under Scandinavian conditions - A. Sigrun Dahlin; Maria Stenberg; Håkan Marstorp (Nutrient Cycling in Agroecosystems, 2011)

fMRI memory assessment in healthy subjects: a new approach to view lateralization data at an individual level - Maria Strandberg; Christina Elfgren; Peter Mannfolk; Johan Olsrud; Lars Stenberg; Danielle van Westen; Elna-Marie Larsson; Ia Rorsman; Kristina Källén (Brain Imaging and Behavior, 2011)

Cutting regime affects the amount and allocation of symbiotically fixed N in green manure leys - A. Sigrun Dahlin; Maria Stenberg (Plant and Soil, 2010)